How do students create and manipulate geometric figures in HOTS-based cuboid problems? - Aliyah Is Karimah; Abi Suwito; Reza Ambarwati; Susanto Susanto; Lela Nur Safrida (AXIOM : Jurnal Pendidikan dan Matematika, 2025)
Geometric intuition is a cognitive skill that supports students in solving geometry problems, one of the more challenging branches of mathematics. This study explores students' ability to create and manipulate geometric figures when working on Higher Order Thinking Skills (HOTS) problems involving cuboids. Employing a qualitative descriptive approach, the study involved 29 eighth-grade students. Data were collected through HOTS-based problem-solving tests and validated interview protocols. Students' abilities to mentally construct and transform geometric figures were assessed using two indicators: (1) visualizing shapes based on imagination and (2) generating new geometric configurations. The findings revealed that most students were unaware of alternative geometric forms embedded within the problem context. The study concludes that students across all performance levels, from low to high, demonstrated the ability to visualize shapes based on imagination. However, only students in the medium category were able to generate a new shape in one problem, whereas those in the high category successfully created new shapes in two problems.